National origin wage differentials in France: evidence from matched employer-employee data - Romain Aeberhardt; Julien Pouget (Institute for the Study of Labor (IZA), 2007)
This paper attempts to explain national origin wage differentials in France. Our data come from a matched employer-employee wage survey performed in 2002. Business survey data are matched to many individual-level variables collected in a household survey. The sample of professionals is decomposed into several sub-samples: within each gender, a distinction is made according to the parents' birthplace (France, North Africa and Southern Europe). We perform a switching regression model of wage determination and occupational employment. Our results suggest that earnings differentials mostly reflect differences in the type of jobs taken up by individuals, according to their experience, background and education. This leads us to favor an interpretation in terms of a certain degree of occupational segregation, rather than mere wage discrimination.
urn:nbn:de:101:1-20080401517
Keywords: 330; Lohndifferenzierung; Ethnische Diskriminierung; Migranten; Arbeitsmarktdiskriminierung; Frankreich